Hip: Anatomy and US technique - Molini, L. (Elsevier, 2011)
Ultrasound (US) has always had a relatively limited role in the evaluation of the hip due to the deep location of this joint. However, many hip diseases are well detectable at US, but before approaching such a study it is necessary to be thoroughly familiar with the normal anatomy and related US images. The study technique is particularly important as optimization of various parameters is required, such as probe frequency, focalization, positioning of the probe, etc. Also the patient’s position is important, as it varies according to the area requiring examination. For the study of the anterior structures, the patient should be in the supine position; for the medial structures, the leg should be abducted and rotated outward with the knee flexed; for the lateral structures, the patient should be in the controlateral decubitus position; for the posterior structures the patient must be in the prone position. US study of the hip includes assessment of the soft tissues, tendons, ligaments and muscles, and also of the bone structures, joint space and serous bursae. The purpose of this article is to review the normal anatomy of the hip as well as the US anatomy of this joint.